2018
DOI: 10.1177/1753193418778999
|View full text |Cite
|
Sign up to set email alerts
|

Pain and outcomes of carpal tunnel release under local anaesthetic with or without a tourniquet: a randomized controlled trial

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…The operations for the present case series were performed under brachial plexus block with a tourniquet in the upper aim or under general anaesthesia. We have noted recent reports of using local anaesthesia without a tourniquet in replantation or flap transfer in the hand (Iqbal et al., 2018; Wong et al., 2017, Xing and Mao, 2018a, 2018b) and using local anaesthesia in hand surgery is becoming popular (Gong and Xing, 2017; Lalonde, 2017, Teo et al., 2013). We also use this approach rather extensively.…”
Section: Discussionmentioning
confidence: 99%
“…The operations for the present case series were performed under brachial plexus block with a tourniquet in the upper aim or under general anaesthesia. We have noted recent reports of using local anaesthesia without a tourniquet in replantation or flap transfer in the hand (Iqbal et al., 2018; Wong et al., 2017, Xing and Mao, 2018a, 2018b) and using local anaesthesia in hand surgery is becoming popular (Gong and Xing, 2017; Lalonde, 2017, Teo et al., 2013). We also use this approach rather extensively.…”
Section: Discussionmentioning
confidence: 99%
“…Literature search did not show any direct comparison regarding these modalities. Nevertheless, Iqbal et al (14) published a study in 2018 in which they randomized Carpal tunnel release cases to undergo either local anesthesia plus adrenaline or local anesthesia plus tourniquet and they found that early pain score was significantly higher in the latter group. Gunasagaran et al (15) compared WALANT technique to local anesthesia plus tourniquet in 72 cases with minor hand surgery and they reported lower early postoperative pain in subjects undergoing WALANT technique.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, to the authors' knowledge, there is no systematic analysis specifically deals with endoscopic CTR with WALANT, although numerous studies assessed WALANT for open CTR with good results. 5,6 We report a prospective case series assessing the patient and surgeon experience, as well as complications with WALANT for single-port endoscopic CTR.…”
mentioning
confidence: 99%